Liquid crystal compound and composition with high-definition bright spots and low dielectric loss
By adopting the liquid crystal compound of general formula (I), using palladium catalytic coupling method to establish a molecular framework and transform functional groups, the problem of large dielectric loss of liquid crystal materials at high frequency is solved, and low dielectric loss, high resistivity and The effect of high dielectric anisotropy is suitable for high-frequency components in high-temperature environments.
Patent Information
- Application Number
- CN202111598781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-12-24
AI Technical Summary
The existing liquid crystal materials have a large dielectric loss at high frequencies, making it difficult to meet the working requirements of high-frequency components in harsh environments, especially the dielectric constant at low frequencies and the resistivity is low, making it difficult to adapt to active driver devices. need.
Using a liquid crystal compound with the general formula (I), a molecular framework is established through palladium catalytic coupling method, and the target structure is obtained through functional group transformation, avoiding the problem of lateral introduction of fluorine atoms, thereby reducing dielectric loss and increasing Resistivity.
The extremely low dielectric loss, large dielectric anisotropy and high resistivity of liquid crystal materials at high frequencies are achieved, which significantly improves the working characteristics of liquid crystal compositions in high temperature environments and reduces dielectric loss.
Smart Images

Figure CN116333755B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of liquid crystal material technology, and specifically relates to a liquid crystal compound and composition with high-definition bright spots and low dielectric loss, which is mainly suitable for filters, adjustable frequency selective surfaces, phase shifters, phased array radars, satellite navigation, and 5G communication networks. Background Art
[0002] In recent years, the application of liquid crystal materials with low dielectric loss and high dielectric tuning rate in liquid crystal microwave device technologies such as smart antennas, filters, adjustable frequency selective surfaces, phase shifters, phased array radars, and 5G communication networks has attracted much attention.
[0003] The dielectric loss of liquid crystal materials is an important factor affecting the insertion loss of microwave devices. In order to obtain high-quality liquid crystal microwave devices, the dielectric loss of liquid crystal materials must be reduced as much as possible. For liquid crystal materials, the loss tangent varies with the direction of the liquid crystal molecules in the electric field, that is, the loss of the long axis and short axis of the liquid crystal molecules is different. When calculating the loss of liquid crystal materials, the maximum loss is generally used as the dielectric loss value of the liquid crystal material. In addition, the dielectric tuning rate of the liquid crystal material determines the microwave device max (tanδ ∥ ,tanδ ⊥ ) tuning capability, and its dielectric tuning rate is determined by the dielectric anisotropy (Δε) of the liquid crystal material under microwaves and the dielectric constant (ε ∥ ) is determined by the ratio:
[0004] τ=Δε / ε ∥ ;
[0005] In order to comprehensively evaluate the performance of liquid crystal materials at high frequencies, the quality factor (η) is introduced:
[0006] η=τ / max(tanδ ∥ ,tanδ ⊥ );
[0007] That is, the smaller the loss of the liquid crystal material and the greater the tuning rate, the greater the quality factor, which means that the performance of the liquid crystal material is better.
[0008] The nematic phase temperature range of the liquid crystal material determines the operating temperature range of the liquid crystal microwave device. The wider the nematic phase temperature range of the liquid crystal material, the wider the operating temperature range of the microwave device. In order to meet the requirements of high-frequency components working under electric field drive, the liquid crystal material is also required to have an appropriate dielectric constant at low frequencies, such as 1KHz. Isothiocyanate liquid crystal compounds have higher birefringence and greater dielectric anisotropy than conventional fluorine-containing liquid crystals, and have higher birefringence and lower rotational viscosity than cyano liquid crystals, and especially have lower dielectric losses.
[0009] Microwave antenna components using liquid crystal materials also need to meet the harsh outdoor working environment requirements, especially low crystallization temperature and high clearing point. In high-power microwave antennas, the device will generate a lot of heat during operation, causing the temperature to rise. However, the dielectric constant and dielectric loss of liquid crystal materials change significantly with temperature at high frequencies, and there is an urgent need to develop materials that are insensitive to changes in ambient temperature.
[0010] In addition, for liquid crystal devices, especially actively driven devices, such as thin film transistor driven devices, liquid crystal materials are also required to have a higher resistivity or voltage holding rate. Existing liquid crystal materials based on isothiocyanate, in order to improve the liquid crystal phase performance, mostly introduce one or more fluorine atoms in the lateral direction of the molecular long axis. Since isothiocyanate itself has a large polarity, and the introduction of fluorine atoms further increases the molecular polarity, the resistivity of the isothiocyanate liquid crystal material based on fluorine substitution is low, which is difficult to adapt to the needs of active drive devices. At the same time, due to the presence of fluorine substituents, the molecular dipole moment increases, and the dielectric loss is relatively large at high frequencies. Summary of the invention
[0011] In order to overcome the defects or shortcomings in the background technology, the present invention provides a liquid crystal compound and its composition with high bright spots, low dielectric loss, high adjustability, low melting point, wide nematic phase temperature range and low temperature sensitivity, as well as a high-frequency component containing the composition.
[0012] In order to achieve the above tasks, the present invention adopts the following technical solutions:
[0013] A liquid crystal compound, the general structural formula of which is shown in formula (I):
[0014]
[0015] Among them, ring A and ring B are cyclohexyl, cyclohexenyl or benzene ring; one of X1~X4 is methyl, and the rest are hydrogen atoms; R is a straight-chain alkyl, straight-chain alkoxy, straight-chain fluoroalkyl with 1 to 9 carbon atoms or an alkenyl or alkenyloxy with 2 to 9 carbon atoms; m and n are 0 or 1.
[0016] The liquid crystal compound of the present invention is preferably selected from the compounds represented by the following structural formula:
[0017]
[0018]
[0019] Wherein R is a straight-chain alkyl group having 1 to 9 carbon atoms or an alkenyl group having 2 to 7 carbon atoms; one of X1 to X4 is a methyl group, and the rest are hydrogen atoms.
[0020] The liquid crystal compound of the present invention is further preferably selected from the compounds represented by the following structural formula:
[0021]
[0022] Here, R is a straight-chain alkyl group having 1 to 9 carbon atoms or an alkenyl group having 2 to 7 carbon atoms.
[0023] The liquid crystal compound of the present invention can be used to establish a molecular skeleton by a palladium-catalyzed coupling method, and then the target structure can be obtained by converting the functional groups. The palladium-catalyzed coupling method includes Suzuki coupling and Sonogashira coupling; the obtained aniline intermediate reacts with thiophosgene to convert the amine group into an isothiocyanate. The palladium catalyst includes bis(triphenylphosphine)palladium chloride; tetrakistriphenylphosphine palladium, etc.
[0024] Specifically, for biphenyl molecular structures, the following synthetic routes can be used for preparation:
[0025]
[0026] (I) Synthesis route of biphenyl tetracyclic isothiocyanate liquid crystals;
[0027] For the molecular structure of diphenylacetylene, the following synthetic route can be used for preparation:
[0028]
[0029] (ii) Synthesis route of diphenylacetylene tetracyclic isothiocyanate liquid crystals;
[0030] The liquid crystal compound of the present invention has the advantages of extremely high clearing point, extremely low dielectric loss in high-frequency band, and large dielectric anisotropy, which can significantly improve the working characteristics of liquid crystal compositions and high-frequency components under high-temperature environment and reduce their dielectric loss. At the same time, since it does not contain lateral fluorine atoms, it has the characteristics of high resistivity.
[0031] Another object of the present invention is to provide a liquid crystal composition comprising the compound represented by general formula (I) as the first component, with a mass ratio of 1% to 40%.
[0032]
[0033] Among them, ring A and ring B are cyclohexyl, cyclohexenyl or benzene ring; one of X1~X4 is methyl, and the rest are hydrogen atoms; R is a straight-chain alkyl, straight-chain alkoxy, straight-chain fluoroalkyl with 1 to 9 carbon atoms or an alkenyl or alkenyloxy with 2 to 9 carbon atoms; m and n are 0 or 1.
[0034] According to the liquid crystal composition of the present invention, the preferred mass ratio of the compound of formula (I) is 5% to 35%, and the more preferred mass ratio is 10% to 30%.
[0035] According to the liquid crystal composition of the present invention, the preferred compound of general formula (I) has the following specific structure:
[0036]
[0037] Here, R is a straight-chain alkyl group having 1 to 9 carbon atoms or an alkenyl group having 2 to 7 carbon atoms.
[0038] According to the liquid crystal composition of the present invention, the compound represented by the general formula (II) is included as the second component, and its mass ratio is 50% to 90%;
[0039]
[0040] The compound represented by the general formula (III) is contained as the third component, and its mass ratio is 0 to 30%.
[0041]
[0042] Among them, R2~R4 are straight-chain alkyl, straight-chain alkoxy, fluoroalkyl with 1 to 9 carbon atoms or alkenyl, alkenyloxy with 2 to 9 carbon atoms; ring C is cyclohexane, cyclohexenyl, benzene ring; o, p are 0 or 1; X5~X6 are -H or -CH3.
[0043] According to the liquid crystal composition of the present invention, the preferred mass ratio of the compound of formula (II) is 55% to 85%, and the more preferred mass ratio is 60% to 80%.
[0044] According to the liquid crystal composition of the present invention, the preferred mass ratio of the compound of formula (III) is 3% to 25%, and the more preferred mass ratio is 5% to 20%.
[0045] According to the liquid crystal composition of the present invention, the specific structural formula of the compound of general formula (II) is further preferred as follows:
[0046]
[0047] According to the liquid crystal composition of the present invention, the specific structural formula of the compound of general formula (III) is further preferred as follows:
[0048]
[0049] The liquid crystal composition according to the present invention may further contain 0.001-1% of additives, such as 2,6-di-tert-butylphenol antioxidants, hindered amine light stabilizers, such as T770, and the like.
[0050] The liquid crystal composition according to the present invention is composed of a plurality of compounds, preferably 3 to 20 compounds, more preferably 5 to 18 and more preferably 7 to 15 compounds. These compounds can be mixed in a conventional manner: the various compounds are weighed according to a predetermined mass ratio, and then heated and heated, and mixed homogeneously by magnetic stirring or ultrasonic stirring until each component is completely dissolved; and then filtered to obtain. The liquid crystal composition can also be prepared in other conventional ways, for example, using a so-called premix, or using a so-called "multi-bottle" system, the components of which are themselves ready-to-use mixtures.
[0051] The performance of liquid crystal at high frequencies was tested using the test method reported in the literature: Penirschke, A. (2004). Cavityperturbation method for characterization of liquid crystals up to 35 GHz. Microwave Conference,2004.34th European.
[0052] Liquid crystal is introduced into polytetrafluoroethylene (PTFE) or fused silica capillary, and the filled capillary is introduced into the middle of a chamber with a resonance frequency of 19 GHz. Then an input signal source is applied, and the result of the output signal is recorded with a vector network analyzer. The changes in the resonance frequency and Q factor between the capillary filled with liquid crystal and the blank capillary are measured, and the dielectric constant and loss tangent are calculated. The dielectric constant components perpendicular and parallel to the liquid crystal director are obtained by the alignment of the liquid crystal in a magnetic field, and the direction of the magnetic field is set accordingly, and then rotated 90° accordingly.
[0053] The preferred liquid crystal composition of the present invention has a tuning rate τ≥0.27, more preferably ≥0.30; the preferred liquid crystal material has a vertical dielectric loss tanδ ⊥ ≤0.006, more preferably tanδ ⊥ ≤0.005; material quality factor η≥45, preferably η≥50. The preferred liquid crystal composition of the present invention has a nematic phase temperature range of -20 to 160°C or above, preferably a nematic phase temperature range of -30 to 180°C or above; the preferred liquid crystal composition has a dielectric constant of ≥7.0 at a low frequency of 1KHz, more preferably ≥8.0.
[0054] Due to the adoption of the above technical solution, the technical progress achieved by the present invention is:
[0055] The liquid crystal compound of the present invention has an extremely high clearing point and extremely low dielectric loss. The liquid crystal composition containing the compound of the present invention has an extremely high clearing point and greatly reduces the temperature sensitivity of the dielectric properties, and is very suitable for high-frequency devices working in high-temperature environments.
[0056] The liquid crystal composition of the present invention has an extremely wide liquid crystal phase operating temperature range, extremely low dielectric loss, high resistivity, and excellent environmental adaptability, especially high-frequency components in high-temperature working environments, and is particularly suitable for smart antenna liquid crystal phase shifters and 5G communication network fields. DETAILED DESCRIPTION
[0057] The present invention is further described in detail below in conjunction with specific embodiments.
[0058] The purity test of the intermediates and products in the examples was conducted by GC (gas chromatography), and the testing instrument was Agilent's 7820 gas chromatograph; LC stands for high performance liquid chromatography, and the testing instrument was Agilent's 1260 liquid chromatograph; 1 H NMR stands for hydrogen nuclear magnetic resonance. 13 C NMR stands for carbon nuclear magnetic resonance spectroscopy, and the testing instrument is Bruker's Advanced 500 MHz nuclear magnetic resonance instrument; GC-MS stands for gas chromatography-mass spectrometry, and the testing instrument is Agilent's MS5975C gas chromatography-mass spectrometry instrument.
[0059] The physical property test methods of liquid crystal compounds are as follows:
[0060] Clearing point (T ni ): Polarized light hot stage method: Apply the liquid crystal sample on a glass slide and place it in an orthogonal polarized light microscope hot stage. Set the heating rate to 3°C / min. Observe the temperature at which the liquid crystal sample changes from bright to dark, which is the clearing point. Differential scanning calorimetry: Under nitrogen protection, set the heating rate to 3°C / min.
[0061] The physical properties test method of liquid crystal compound at high frequency: add it to the basic formula (Host) at a mass ratio of 15%, and use vector network analyzer and cavity perturbation method to test the dielectric anisotropy Δε, dielectric tuning rate τ and dielectric loss (tanδ ∥ ,tanδ ⊥ ), and the quality factor η is calculated. Preparation method of liquid crystal composition: adopt thermal dissolution method. First, use a precision balance to weigh monomer liquid crystals of different weight proportions, heat to 60℃~100℃, and stir and mix for 1~2 hours to make each component dissolve evenly. After cooling, filter, and degas the filtered liquid in high vacuum (≤100Pa), and finally encapsulate it with high-purity nitrogen to obtain the target mixed liquid crystal.
[0062] Unless otherwise specified, the liquid crystal compositions of the present invention are prepared according to this method.
[0063] The mixed liquid crystal is tested for physical properties and photoelectric properties. The detailed test methods for the physical properties and photoelectric properties involved in the present invention are as follows:
[0064] (1) Clearing point (Tni):
[0065] Polarized light hot stage method: Apply the liquid crystal sample on a glass slide and place it in an orthogonal polarized light microscope hot stage, and set the heating rate to 2°C / min. The temperature at which the liquid crystal sample starts to turn black from bright state under a polarized light microscope is the clearing point.
[0066] Alternatively, differential scanning calorimetry was used: under nitrogen atmosphere, the heating rate was set to 2°C / min.
[0067] (2) Low temperature storage temperature (LTS): Place about 1 mL of mixed liquid crystal into a transparent glass bottle and place it in a low temperature refrigerator. Set the temperature to -20℃, -30℃, and -40℃, store for 10 days respectively, and observe whether there is crystal precipitation or smectic phase. If no crystal precipitation occurs at -30℃, LTS ≤ -30℃.
[0068] (3) Birefringence (Δn): Using an Abbe refractometer, at a constant temperature of 25°C and a light source of 589 nm, the ordinary light (n o ) and extraordinary light (n e ) refractive index, birefringence Δn = n e -n o .
[0069] (4) Dielectric constant (Δε): Tested with an LCR meter at a constant temperature of 25°C. Δε = ε ∥ -ε ⊥ , that is, the dielectric constant along the long axis of the molecule (ε ∥ ) and the dielectric constant along the molecular short axis (ε ⊥ ) is the difference between .
[0070] (5) Elastic constant (K 11 , K 33 ): Under the condition of 25℃ constant temperature, the capacitance-voltage (CV) curve of liquid crystal is tested and K is obtained by fitting. 11 and K 33 .
[0071] (6) Rotational viscosity (γ1): Under a constant temperature of 25°C, by applying voltage to the liquid crystal test box, the instantaneous current value Ip of the liquid crystal molecules deflected by the electric field movement is tested, and the rotational viscosity γ1 is calculated.
[0072] (7) Resistivity (ρ): At a constant temperature of 25°C, 0.5 mL of liquid crystal was added to the LE-21 liquid electrode, a voltage of 10 V was applied, the corresponding current was measured, and the liquid crystal resistivity was calculated.
[0073] Code and Description:
[0074] (1) Physical parameters
[0075] Code illustrate unit <![CDATA[T cl ]]> Clear Point ℃ <![CDATA[T m ]]> Low melting point ℃ <![CDATA[ε ⊥ ]]> Dielectric constant perpendicular to the director <![CDATA[ε ∥ ]]> Dielectric constant parallel to the director Δε Dielectric Anisotropy Δn Birefringence <![CDATA[γ1]]> Rotational viscosity mPa·s <![CDATA[K 11 ]]> Splay elastic constant pN <![CDATA[K 33 ]]> Bending elastic constant pN <![CDATA[tanδ ∥ ]]> Dielectric loss tangent perpendicular to the director <![CDATA[tanδ ⊥ ]]> Dielectric loss tangent perpendicular to the director η Quality Factor ρ Resistivity Ω·cm
[0076] (2) Structural abbreviations
[0077]
[0078]
[0079] For example:
[0080]
[0081] Liquid crystal phase transition temperature: C represents melting point, S represents smectic phase, N represents nematic phase, and Iso represents liquid state.
[0082] Example 1: Synthesis of 4-isothiocyanate-2-methyl-4″-(4-pentylcyclohexyl)-1,1′:4′,1″-terphenyl
[0083] The specific structural formula is as follows:
[0084]
[0085] The preparation process is as follows:
[0086] Step 1: Preparation of intermediate boronate
[0087]
[0088] Under nitrogen protection, add 23.1g of 4-bromo-4′-(4-pentylcyclohexyl)-1,1′-biphenyl, 16.8g of biboric acid pinacol ester, 21.2g of potassium acetate, 1.3g of [1,1′-bis(diphenylphosphinoferrocene)] palladium dichloride (Pd(dppf)Cl2), and 200ml of tetrahydrofuran (THF) to a 500ml three-necked flask, and stir to dissolve. Heat to reflux reaction for 6h, stop heating, cool and stir overnight. Extract with toluene, wash with water three times and dry. Evaporate toluene under reduced pressure, pass the residue through a silica gel column, and elute with n-heptane. The product is recrystallized to obtain a white solid.
[0089] Step 2: Synthesis of 2-methyl-4"-(4-pentylcyclohexyl)-[1,1':4',1"-terphenyl]-4-amine
[0090] The specific structure is as follows:
[0091]
[0092] Under nitrogen protection, add 2.2g of intermediate borate, 1.4g of 3-methyl-4-iodoaniline, 0.07g of bis(triphenylphosphine)palladium dichloride (Pd(PPh3)2Cl2), 2.1g of potassium carbonate, 10ml each of toluene, ethanol and water to a 250ml single-mouth bottle. Heat to reflux reaction for 6h. Stop heating and cool naturally, extract with toluene, wash with water, dry and spin dry. Recrystallize to obtain 2.0g of white solid.
[0093] Step 3: Synthesis of 4-isothiocyanate-2-methyl-4″-(4-pentylcyclohexyl)-1,1′:4′,1″-terphenyl
[0094] The specific structure is as follows:
[0095]
[0096] Add 2.0 g of 2-methyl-4'-(4-pentylcyclohexyl)-[1,1'-biphenyl]-4-amine, 20 mL of tetrahydrofuran, and 0.84 g of thiophosgene to the reaction flask, and stir at room temperature for 2 h. Remove the solvent by rotary evaporation, add toluene to dissolve the obtained solid, wash with water until neutral, and dry over anhydrous magnesium sulfate. Filter, evaporate the filtrate to dryness, add n-heptane, and purify by column chromatography. Recrystallize to obtain 1.2 g of white solid with a liquid chromatography purity of 99.9%.
[0097] Structure identification:
[0098] 1 H NMR(δ,CDCl3):0.90(t,3H),1.17–1.62(m,15H),1.82-1.86(m,2H),2.52(s, 3H),2.71(t,1H),7.25(m,5H),7.38(d,2H),7.51-7.54(m,3H),7.76(d,1H).
[0099] The phase transition temperature of 4-isothiocyanate-2-methyl-4″-(4-pentylcyclohexyl)-1,1′:4′,1″-terphenyl was tested by DSC at a temperature increase of 5° C. / min. The result was: C 118.1N 289.3Iso.
[0100] Example 2: Synthesis of 4-isothiocyanate-2-methyl-4″-(4-propylcyclohexyl)-1,1′:4′,1″-terphenyl
[0101] The specific structure is as follows:
[0102]
[0103] 4-Bromo-4′-(4-propylcyclohexyl)-1,1′-biphenyl was used to replace 4-bromo-4′-(4-pentylcyclohexyl)-1,1′-biphenyl in step (1) of Example 1, and 4-isothiocyanate-2-methyl-4″-(4-propylcyclohexyl)-1,1′:4′,1″-terphenyl was synthesized using the same method as Example 1.
[0104] Structure identification:
[0105] 1 H NMR(δ,CDCl3):0.90(t,3H),1.17–1.62(m,11H),1.82-1.86(m,2H),2.52(s, 3H),2.71(t,1H),7.25(m,5H),7.38(d,2H),7.51-7.54(m,3H),7.76(d,1H).
[0106] The phase transition temperature of 4-isothiocyanate-2-methyl-4″-(4-propylcyclohexyl)-1,1′:4′,1″-terphenyl was tested by DSC at a temperature increase of 5° C. / min. The result was: C 123N 309.4Iso.
[0107] Example 3: Synthesis of 4-isothiocyanate-2-methyl-4″-(4-butylcyclohexyl)-1,1′:4′,1″-terphenyl
[0108] The specific structure is as follows:
[0109]
[0110] 4-Bromo-4′-(4-pentylcyclohexyl)-1,1′-biphenyl was used to replace 4-bromo-4′-(4-pentylcyclohexyl)-1,1′-biphenyl in step (1) of Example 1, and 4-isothiocyanate-2-methyl-4″-(4-butylcyclohexyl)-1,1':4′,1″-terphenyl was synthesized using the same method as Example 1.
[0111] Structure identification:
[0112] 1 H NMR(CDCl3,500MHz)δ(ppm):0.90(t,3H),1.17–1.62(m,17H),1.82-1.86(m,2H),2 .52(s,3H),2.71(t,1H),7.25(m,5H),7.38(d,2H),7.51-7.54(m,3H),7.76(d,1H). .
[0113] The liquid crystal phase transition temperature of 4-isothiocyanate-2-methyl-4″-(4-butylcyclohexyl)-1,1′:4′,1″-terphenyl was tested by DSC at a temperature increase of 5° C. / min. The result was: C 103.7N 301.9Iso.
[0114] Example 4: Synthesis of 4-((4-isothiocyanato-2-methylphenyl)ethynyl)-4'-(4-propylcyclohexyl)-1,1'-biphenyl
[0115] The specific structure is as follows:
[0116]
[0117] Step 1: Synthesis of 4-iodo-4'-(4-propylcyclohexyl)-1,1'-biphenyl
[0118] The specific structure is as follows:
[0119]
[0120] Add 53.2g of 4-(4-propylcyclohexyl)-1,1'-biphenyl into a 500ml three-necked flask, add 7.4g of iodic acid, 50ml of 15% sulfuric acid, 70ml of dichloromethane, and 160ml of acetic acid, heat to reflux, add 21.35g of iodine in batches, and stop heating after reacting for 2h. Add sodium thiosulfate solution for washing, and filter to obtain a solid. Recrystallize from toluene to obtain 59.8g of pure product with a purity of 99.2%.
[0121] Step 2: Synthesis of trimethyl((4'-(4-propylcyclohexyl)-[1,1'-biphenyl]-4-yl)ethynyl)silane
[0122] The specific structure is as follows:
[0123]
[0124] Under nitrogen protection, add 4-iodo-4'-(4-propylcyclohexyl)-1,1'-biphenyl (40.4g), 300ml triethylamine, 500ml tetrahydrofuran, Pd(PPh3)2Cl2 (0.7g), triphenylphosphine (0.57g), cuprous iodide (0.79g) into a three-necked flask, heat to 60°C, dropwise add 100ml triethylamine solution containing 14.7g trimethylsilylene, continue to react for 4h after the addition, and then cool naturally. Filter, concentrate the filtrate, pass the residue through a silica gel column, and elute with n-heptane. Evaporate the solvent to obtain 36.5g of light yellow solid with a purity of 98.6%.
[0125] Step 3: Synthesis of 4-ethynyl-4'-(4-propylcyclohexyl)-1,1'-biphenyl
[0126] The specific structure is as follows:
[0127]
[0128] Under nitrogen protection, add trimethyl ((4'-(4-propylcyclohexyl)-[1,1'-biphenyl]-4-yl)ethynyl) silane (36.5g), 200ml ethanol, 300ml tetrahydrofuran, and 1.68g potassium hydroxide to a three-necked flask and stir to react for 2h. Evaporate the solvent, add toluene for extraction, and wash with water until neutral. Evaporate the toluene, and recrystallize from ethanol to obtain 25.1g of light yellow solid.
[0129] Step 4: Synthesis of 3-methyl-4-((4'-(4-propylcyclohexyl)-[1,1'-biphenyl]-4-yl)ethynyl)aniline
[0130] The specific structure is as follows:
[0131]
[0132] Under nitrogen protection, add 3-methyl-4-iodoaniline (11.65g), 50ml triethylamine, Pd(PPh3)2Cl2 (0.35g), triphenylphosphine (0.39g), cuprous iodide (0.29g) to a three-necked flask, heat to 55°C, and dropwise add 200ml tetrahydrofuran solution containing 15.1g 4-ethynyl-4'-(4-propylcyclohexyl)-1,1'-biphenyl. After the dropwise addition, continue the reaction for 4h. Filter and evaporate the solvent. Add toluene and wash with water. Evaporate part of the toluene and freeze and crystallize to obtain 17.3g of solid.
[0133] Step 5: Synthesis of 4-((4-isothiocyanato-2-methylphenyl)ethynyl)-4'-(4-propylcyclohexyl)-1,1'-biphenyl
[0134] The specific structure is as follows:
[0135]
[0136] In a three-necked flask, add 10.5 g of 3-methyl-4-((4'-(4-propylcyclohexyl)-[1,1'-biphenyl]-4-yl)ethynyl)aniline and 200 ml of tetrahydrofuran. Add 4.4 g of thiophosgene dropwise and react at room temperature for 3 hours. Evaporate the solvent and pass the residue through a silica gel column and elute with toluene. Evaporate the solvent and repeatedly recrystallize the crude product with toluene to obtain 9.2 g of a white solid with a liquid chromatography LC purity of 99.8%.
[0137] Structure identification:
[0138] 1H NMR(CDCl3,500MHz)δ(ppm):0.90(t,3H),1.17–1.62(m,11H),1.82-1.86(m,2H),2.40(s,3H),2 .71(t,1H),6.99-7.02(m,2H),7.38(d,2H),7.51(d,2H),7.54(d,1H),7.62(d,2H),7.74(d,2H).
[0139] The liquid crystal phase transition temperature of 4-((4-isothiocyanato-2-methylphenyl)ethynyl)-4'-(4-propylcyclohexyl)-1,1'-biphenyl was tested by DSC at a temperature increase of 5°C / min. The result was: C 161.09N>300Iso.
[0140] Example 5: 4-((4-isothiocyanato-2-methylphenyl)ethynyl)-4'-(4-butylcyclohexyl)-1,1'-biphenyl
[0141] The specific structure is as follows:
[0142]
[0143] 4-(4-butylcyclohexyl)-1,1'-biphenyl was used to replace 4-(4-propylcyclohexyl)-1,1'-biphenyl in step (1) of Example 4, and 4-isothiocyanate-2-methyl-4"-(4-butylcyclohexyl)-1,1':4',1"-terphenyl was synthesized using the same method as Example 4.
[0144] Structure identification:
[0145] 1 H NMR(CDCl3,500MHz)δ(ppm):0.90(t,3H),1.17–1.62(m,13H),1.82-1.86(m,2H),2.40(s,3H),2 .71(t,1H),6.99-7.02(m,2H),7.38(d,2H),7.51(d,2H),7.54(d,1H),7.62(d,2H),7.74(d,2H).
[0146] The liquid crystal phase transition temperature of 4-((4-isothiocyanato-2-methylphenyl)ethynyl)-4'-(4-butylcyclohexyl)-1,1'-biphenyl was tested by DSC at a temperature increase of 5°C / min. The result was: C140.35 N>300Iso.
[0147] Example 6: 4-((4-isothiocyanato-2-methylphenyl)ethynyl)-4'-(4-pentylcyclohexyl)-1,1'-biphenyl
[0148] The specific structure is as follows:
[0149]
[0150] 4-(4-pentylcyclohexyl)-1,1'-biphenyl was used to replace 4-(4-propylcyclohexyl)-1,1'-biphenyl in step (1) of Example 4, and 4-isothiocyanate-2-methyl-4"-(4-pentylcyclohexyl)-1,1':4',1"-terphenyl was synthesized using the same method as Example 4.
[0151] Structure identification:
[0152] 1 H NMR(CDCl3,500MHz)δ(ppm):0.90(t,3H),1.17–1.62(m,15H),1.82-1.86(m,2H),2.40(s,3H),2 .71(t,1H),6.99-7.02(m,2H),7.38(d,2H),7.51(d,2H),7.54(d,1H),7.62(d,2H),7.74(d,2H).
[0153] The liquid crystal phase transition temperature of 4-((4-isothiocyanato-2-methylphenyl)ethynyl)-4'-(4-pentylcyclohexyl)-1,1'-biphenyl was tested by DSC at a temperature increase of 5°C / min. The result was: C 141.98S 213.65N>300Iso.
[0154] Example 7: 4-(4-((4-isothiocyanato-2-methylphenyl)ethynyl)phenyl)-4'-propyl-1,1'-bicyclohexane
[0155] The specific structure is as follows:
[0156]
[0157] 4-(4-((4-isothiocyanato-2-methylphenyl)ethynyl)phenyl)-4'-propyl-1,1'-bicyclohexane was synthesized by using 4-phenyl-4'-propyl-1,1'-bicyclohexane to replace 4-(4-propylcyclohexyl)-1,1'-biphenyl in step (1) of Example 4.
[0158] Structure identification:
[0159] 1H NMR(CDCl3,500MHz)δ(ppm):0.97(t,3H),1.17–1.66(m,21H),1.82–1.90(m,2H),2 .40(s,3H),2.64(m,1H),7.00-7.15(m,2H),7.28(d,2H),7.47(d,2H),7.56(d,1H).
[0160] The liquid crystal phase transition temperature of 4-(4-((4-isothiocyanato-2-methylphenyl)ethynyl)phenyl)-4'-propyl-1,1'-bicyclohexane was tested by DSC at a temperature increase of 5°C / min. The result was: C 124.86N>350I.
[0161] Embodiment 8:
[0162] The liquid crystal composition M0 is composed of the monomeric liquid crystal compounds shown in Table 1.
[0163] Table 1 Example 8 Liquid crystal composition M0
[0164] Monomer Liquid Crystal Mass ratio / % 2CPUS 25 3CPUS 25 5CPUS 25 3CCV 25
[0165] In order to evaluate the performance of the newly synthesized liquid crystal compound, the compounds of Example 1, Example 6, and Example 7 were uniformly mixed with M0 at a mass ratio of 15:85 to obtain test composition formulas M1 to M3.
[0166] Table 2 Liquid crystal compositions M1 to M3 of Example 8
[0167] Composition Compound Mass ratio (compound: M0) M1 5CPPP(M-3)S 15:85 M2 5CPPTP(M-3)S 15:85 M3 3CCPTP(M-3)S 15:85
[0168] Liquid crystal compositions M0 to M3 were respectively poured into polytetrafluoroethylene tubes, and the dielectric constant and loss tangent value at 19 GHz were tested by cavity perturbation method at 25° C., and the quality factor was calculated. The results are shown in Table 3 below.
[0169] Table 3 High frequency performance parameters of liquid crystal compositions M0 to M3 of Example 8
[0170] Composition ε⊥ ε∥ Δε tanδ⊥ tanδ∥ τ η M0 2.361 2.989 0.628 0.0106 0.0049 0.210 19.82 M1 2.422 3.158 0.736 0.0089 0.0041 0.233 26.19 M2 2.435 3.243 0.808 0.0087 0.0040 0.249 28.62 M3 2.394 3.138 0.744 0.0084 0.0040 0.237 28.21
[0171] From the test data, it can be found that after applying the compound of the present invention, the tanδ of the liquid crystal compositions M1 to M3 is higher than that of M0. ⊥ There is a significant decrease, Δε increases, and η increases significantly, which shows that this type of liquid crystal compound has the advantages of extremely low dielectric loss and high quality factor.
[0172] Embodiment 9:
[0173] Liquid crystal composition M4, the mass ratio and performance parameters of each component are shown in Table 4 below.
[0174] Table 4 Mass ratio and performance parameters of liquid crystal composition M4 in Example 9
[0175]
[0176] Embodiment 10:
[0177] Liquid crystal composition M5, the mass ratio and performance parameters of each component are shown in Table 5 below.
[0178] Table 5 Mass ratio and performance parameters of liquid crystal composition M5 of Example 10
[0179]
[0180] Embodiment 11:
[0181] Liquid crystal composition M6, the mass ratio and performance parameters of each component are shown in Table 6 below.
[0182] Table 6 Mass ratio and performance parameters of the liquid crystal composition of Example 11
[0183]
[0184]
[0185] Comparative Example 1:
[0186] Chinese patent application 202010288457.2 discloses an isothiocyanate liquid crystal having three ring structures, the structure of which is shown below:
[0187]
[0188] Its thermal performance data is C 64.54N 215.27Iso.
[0189] By comparing the thermal properties of the liquid crystal compounds of Examples 1-7 of the present invention, it can be seen that the liquid crystal compounds of the present invention have significantly increased clearing points, which are more conducive to improving the high-temperature clearing points of the liquid crystal composition.
[0190] The monomer liquid crystal was added to the basic formula M0 at a mass percentage of 15% to form the liquid crystal composition M7. The physical properties of the formula were tested at 19 GHz at 25° C. The data are shown in Table 7.
[0191] Table 7 Test data of liquid crystal composition M7 of comparative example 1
[0192] Liquid crystal composition <![CDATA[ε ⊥ ]]> <![CDATA[ε ∥ ]]> ∆ε <![CDATA[tanδ ⊥ ]]> <![CDATA[tanδ ∥ ]]> τ η M7 2.402 3.106 0.704 0.0096 0.0042 0.227 23.65
[0193] By comparing the liquid crystal composition M7 of comparative example 1 with the liquid crystal compositions M1 to M3 of embodiment 8, it can be seen that the liquid crystal compound with a four-ring structure of the present invention has a larger dielectric anisotropy value and significantly reduced dielectric loss at high frequencies, as well as significantly improved adjustability τ and a larger quality factor η.
[0194] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0195] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0196] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A liquid crystal compound with high-definition bright spots and low dielectric loss, characterized in that: The structure is shown in the following table: Wherein R is a straight-chain alkyl group having 1 to 9 carbon atoms or an alkenyl group having 2 to 7 carbon atoms; one of X1 to X4 is a methyl group, and the rest are hydrogen atoms.
2. The liquid crystal compound with high-definition bright spots and low dielectric loss according to claim 1, characterized in that: The specific structure is as follows: 。 3. A liquid crystal composition with high-definition bright spots and low dielectric loss, characterized in that: A liquid crystal compound having high bright spots and low dielectric loss according to any one of claims 1 to 2, containing 1% to 40% by mass; It also contains 50% to 90% by weight of a compound represented by the general formula (II); (Ⅱ); Wherein, R2 is a straight-chain alkyl, straight-chain alkoxy, fluoroalkyl having 1 to 9 carbon atoms or an alkenyl or alkenyloxy having 2 to 9 carbon atoms; ring C is cyclohexane, cyclohexenyl or benzene ring; o and p are 0 or 1 respectively; X5 and X6 are -H or -CH3 respectively.
4. The liquid crystal composition with high-definition bright spots and low dielectric loss according to claim 3, characterized in that: It also contains a compound represented by the general formula (III) with a mass percentage of 0% to 30%; (Ⅲ); Among them, R3 and R4 are respectively straight-chain alkyl, straight-chain alkoxy, fluoroalkyl with 1 to 9 carbon atoms or alkenyl, alkenyloxy with 2 to 9 carbon atoms; ring D and ring E are respectively cyclohexane, cyclohexenyl or benzene ring.
5. The liquid crystal composition with high-definition bright spots and low dielectric loss according to claim 3 or 4, characterized in that: With: tuning rate τ ≥ 0.27, vertical dielectric loss tanδ ⊥ ≤0.006, material quality factor η≥45, nematic phase temperature range is -20~160℃, low frequency 1KHz dielectric constant ≥7.
0.
6. A high-frequency component, characterized in that it is prepared from the liquid crystal composition with high-definition bright spots and low dielectric loss as described in any one of claims 3 to 5.
Citation Information
Patent Citations
Liquid crystal medium for high frequency technology and components thereof
CN113528148A
Liquid crystal composition with extremely low dielectric loss and high-frequency assembly thereof
CN113528154A
Liquid crystal compound with ultralow dielectric loss, composition and high-frequency assembly
CN116332800A